2018
DOI: 10.3389/fmed.2018.00225
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factors and Antibiotic Resistance of Klebsiella pneumoniae Strains Isolated From Neonates With Sepsis

Abstract: Introduction: Klebsiella pneumoniae is one of the most important infectious agents in neonates. There are “classic” and hypervirulent strains of K. pneumoniae. The “classic” non-virulent strain of K. pneumoniae, producing extended-spectrum beta-lactamases (ESBLs), is associated with nosocomial infections. Hypervirulent K. pneumoniae strains are associated with invasive infections in previously healthy adult people, and most of them exhibit antimicrobial susceptibility. The role of virulent strains of K. pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
55
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 44 publications
(51 reference statements)
10
55
1
3
Order By: Relevance
“…In a study conducted by Ranjbar et al (27), apart from rmpA no significant relations were found between the existence of bla CTX-M-15 and virulence genes. Other study furnished the information that the occurrence of β-lactamase or antibiotic resistance genes is related with certain virulence characteristics, particularly rmpA and mrkD which further validates our findings (28). Nevertheless, previous study did not discover any association between these variables (6).…”
Section: Discussionsupporting
confidence: 87%
“…In a study conducted by Ranjbar et al (27), apart from rmpA no significant relations were found between the existence of bla CTX-M-15 and virulence genes. Other study furnished the information that the occurrence of β-lactamase or antibiotic resistance genes is related with certain virulence characteristics, particularly rmpA and mrkD which further validates our findings (28). Nevertheless, previous study did not discover any association between these variables (6).…”
Section: Discussionsupporting
confidence: 87%
“…There are two types of K. pneumoniae strains "classic" (cKp), usually non-virulent and drug-resistant gene producer and usually associated with hospital infections, while the other type is a hypervirulent (hvKp) drugsensitive strain [2]. K. pneumoniae possesses different virulence and antimicrobial resistance genes associated with various clinical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of K. pneumoniae strains "classic" (cKp), usually non-virulent and drug-resistant gene producer and usually associated with hospital infections, while the other type is a hypervirulent (hvKp) drug-sensitive strain [2]. K. pneumoniae possesses different virulence and antimicrobial resistance genes associated with various clinical conditions.…”
Section: Introductionmentioning
confidence: 99%